Analisis Penyebab dan Solusi Masalah Durasi Overhaul Dump Truck Komatsu HD 785-7 Tidak Sesuai Rencana - Latif, Akhmad Abdul; Nurhadi, Nurhadi (Fakultas Teknik UMSU, 2023)
Dump Truck is one of the heavy equipment that functions to transport materials such as soil and coal. For this machine to always be in the best condition, periodic maintenance is required, one of which is overhaul maintenance. There are various types of overhaul work on the Komatsu HD 785-7 dump truck unit. Even though there was good planning before the work started, there were still problems with the duration of the Komatsu HD 785-7 overhaul dump truck work which was not in accordance with the initial plan and resulted in the company as a heavy equipment rental service provider losing money. The purpose of this study is to analyze the causes of the duration of work on the Komatsu HD 785-7 dump truck overhaul and provide a solution as a recommendation or reference for the company. The method used is descriptive quantitative method. Descriptive quantitative methods are used to understand an event regarding the duration of an overhaul that is not according to plan in depth, by describing and explaining the characteristics of the incident. Collecting data by interviewing workers, observing in the field, distributing questionnaires and archives of previous overhaul work documents. The results of the study show that the main cause of the duration of work that is not according to plan is the arrival of spare parts or major components not according to schedule, and the addition of work accompanied by the addition of spare parts. The solution provided is to schedule joint inspection work to be carried out earlier with the aim of being able to find out the additional spare parts needed so that the ordering time can be made earlier and the waiting time for spare parts supply can be reduced.